PENGARUH MODEL QUANTUM TEACHING TERHADAP PRESTASI BELAJAR IPA SISWA KELAS IV SD NEGERI GLAGAH YOGYAKARTA - Rosyana Astri Astari; Tias Ernawati (Universitas Sarjanawiyata Tamansiswa, 2018)
This research is descriptively aimed to know the category of science achievement of fourth grade students of SD Negeri Glagah Yogyakarta in academic year 2017/2018 whose learning using quantum teaching model and direct instruction model. Comparatively to know the difference of science achievement of fourth grade students of SD Negeri Glagah Yogyakarta in the academic year 2017/2018 between learning using quantum teaching model and direct instruction model. This type of research is quasi experiment with nonequivalent control group design. Techniques of collecting data using tests and documentation. The data analysis technique was calculated by using the t-test after the prerequisite analysis test which included the test of distribution normality and variance homogeneity test. Descriptively research show the category of science achievement of fourth grade students of SD Glagah Yogyakarta in the academic year of 2017/2018 whose learning using the quantum teaching model obtained the average of 19,308 including the high category and learning using the direct instruction model obtained the average of 16,077 including the high category. In t-test obtained thitung = 2,398 with p = 0,020, because p=0,05 mean there is a significant difference in science achievement of fourth grades of SD Negeri Glagah Yogyakarta in academic year 2017/2018 between learning using quantum teaching model and direct instruction model. The average score of quantum teaching model is higher than the average score of direct instruction model. It means there is a positive and significant influence of quantum teaching model on the science achievement of fourth grades SD Negeri Glagah Yogyakarta in the academic year 2017/2018.